Upper Gastrointestinal Endoscopy and Histopathology Appearance in Indonesian Children with Recurrent Epigastric Pain - F M Susanto; Badriul Hegar; Agus Firmansyah (The Indonesian Society for Digestive Endoscopy, 2007)
Background: Recurrent Epigastric Pain (REP) is a clinical symptom frequently found in children. Data of the correlation between duration of illness, frequency of illness, associated symptoms of REP and the abnormality of endoscopic and histopathologic appearance are still limited, especially in Indonesia. The role of Helicobacter pylori (H. pylori) infection in causing organic abnormalities of the gastrointestinal tract (GIT) is also still controversial. Aim:To know the endoscopic and histopathologic appearance and the prevalence of Helicobacter pylori infection, 169 children with REP was performed for endoscopic and histopathologic examination in Department of Pediatric, Cipto Mangunkusumo hospital. Result:Endoscopic and histopathologic abnormalities were found significantly in children who suffered from REP more than 9 months and more than 6 times during 3 months of period. Conclusion: Endoscopic and histopathologic examinations should be considered in children with REP. Keywords: recurrent abdominal pain, epigastric pain, Helicobacter pylori, endoscopy and histopathology